2016
DOI: 10.3389/fgene.2016.00011
|View full text |Cite
|
Sign up to set email alerts
|

The MiRNA Journey from Theory to Practice as a CNS Biomarker

Abstract: MicroRNAs (miRNAs), small nucleotide sequences that control gene transcription, have the potential to serve an expanded function as indicators in the diagnosis and progression of neurological disorders. Studies involving debilitating neurological diseases such as, Alzheimer's disease, multiple sclerosis, traumatic brain injuries, Parkinson's disease and CNS tumors, already provide validation for their clinical diagnostic use. These small nucleotide sequences have several features, making them favorable candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 79 publications
1
62
0
Order By: Relevance
“…Therefore, establishment of biomarkers that allows early detection is of utmost importance for the management of these disorders. In this regard, miRNAs can also be isolated from circulating blood cells or CSF, and they are promising non-invasive biomarkers for a wide variety of diseases (Stoicea et al, 2016). …”
Section: Biomarker Discovery Studies On Mirnasmentioning
confidence: 99%
“…Therefore, establishment of biomarkers that allows early detection is of utmost importance for the management of these disorders. In this regard, miRNAs can also be isolated from circulating blood cells or CSF, and they are promising non-invasive biomarkers for a wide variety of diseases (Stoicea et al, 2016). …”
Section: Biomarker Discovery Studies On Mirnasmentioning
confidence: 99%
“…The search for reliable serological markers of mTBI that are easily obtainable in the blood has yielded numerous promising candidates (Table 1). Although there are a number of excellent reviews, book chapters, and even a special issue summarizing current knowledge and identifying future directions in the field (Brody et al, 2015; Dashnaw et al, 2012; Di Battista et al, 2013; Giza and Difiori, 2011; Giza and Hovda, 2001, 2014; Jeter et al, 2013; Kovesdi et al, 2010; Ling et al, 2015; Lorente, 2015; Neher et al, 2014; Papa et al, 2015; Stoicea et al, 2016; Zetterberg and Blennow, 2015), rarely are potential blood biomarkers for mTBI discussed in terms of cellular origin and function. In continuing to validate existing serological biomarkers, it is important to understand their fundamental biological functions within the body and to explore the clinical implications of their increased presence in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of their gene expression showed that these miRNA species were expressed in the brain tissue, the plasma/serum/placenta, or in a combination of these at relatively high levels. Current evidence suggests that the blood-brain barrier does not block the passage of miRNAs between CSF and blood, even if brain-derived miRNAs are somewhat more diluted in blood (Stoicea et al, 2016). While the data on the penetration of miRNA from peripheral tissues to the brain are limited, one can assume that this transfer is highly possible, especially during embryonic development when brain tissue and its compartmentalization is not yet fully formed.…”
Section: Discussionmentioning
confidence: 99%